2018
DOI: 10.1103/physrevb.98.075142
|View full text |Cite
|
Sign up to set email alerts
|

Majorana oscillations modulated by Fano interference and degree of nonlocality in a topological superconducting-nanowire–quantum-dot system

Abstract: We explore theoretically the influence of Fano interference in the so-called Majorana oscillations in a T-shaped hybrid setup formed by a quantum dot (QD) placed between conducting leads and sidecoupled to a topological superconducting nanowire (TSNW) hosting zero-energy Majorana bound states (MBSs) at the ends. Differential conductance as a function of the external magnetic field reveals oscillatory behavior. Both the shape and amplitude of the oscillations depend on the biasvoltage, degree of MBSs non-locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…They are connected to leads L and R by tunnel couplings, VL,ktrue(jtrue) and VR,ktrue(jtrue) (j=1,2). It should be noted that they depend on the state k (k) in lead L ( R ) in the presence of multiple channels in the leads, whereas the tunnel couplings are assumed to be independent of the states in the leads in almost all the previous papers . The chemical potentials in the leads are μL and μR with bias voltage eV=μLμR between them.…”
Section: Model and Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are connected to leads L and R by tunnel couplings, VL,ktrue(jtrue) and VR,ktrue(jtrue) (j=1,2). It should be noted that they depend on the state k (k) in lead L ( R ) in the presence of multiple channels in the leads, whereas the tunnel couplings are assumed to be independent of the states in the leads in almost all the previous papers . The chemical potentials in the leads are μL and μR with bias voltage eV=μLμR between them.…”
Section: Model and Calculation Methodsmentioning
confidence: 99%
“…A similar model was also examined for the phase measurement in the Kondo regime in the multi‐terminal geometry . Very recently, the Fano resonance was proposed to use for the detection of the Majorana bound states …”
Section: Introductionmentioning
confidence: 99%
“…This is quite different from the Josephson current with 2π periodicity in the usual junctions. Meanwhile, there were also some proposes of hybridizing a quantum dot (QD) to one end of a TSNW [16][17][18][19][20] in that the information of the MBSs will "leak" into the QD and then can be detected by spectroscopy transport measurements in a noninvasive way [21,22]. Some other proposals such as the thermoelectric effect [23] and optical schemes [24,25] based on QDs were also put forward.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting development is the coupling of quantum dots (QDs) to one of the edges of a TSQW [2,[12][13][14][15][16][17][18][19]. It has been shown that the MZM "leaks" into the quantum dot, a phenomena that can be possibly observed by spectroscopy transport measurements by coupling the QD to source and drain leads [20,21].…”
Section: Introductionmentioning
confidence: 99%